Internet access and use among adults aged over 50 and over in Ireland; Results from Wave 5 of the Irish Longitudinal Study on Ageing. - Kenny, Rose; Scarlett, Siobhan; Hever, Ann; Doody, Paul (My University, 2020)
This report will outline internet access and use among adults aged 50 years and over in Ireland. These analyses are based on data from wave 5 of the Irish Longitudinal Study on Ageing (TILDA), collected in 2018. These analyses have been conducted presently in the context of the Coronavirus Disease-2019 (COVID-19) pandemic, when access to the internet has become increasingly important to many people in their working and personal lives. It is the latest in a series of reports produced by TILDA, aimed at helping the response to, and understanding of the pandemic in Ireland (1-6). Public health measures introduced by the Irish government in response to the COVID-19 pandemic have included social distancing, and encouragement of older adults and those with underlying health conditions to stay at home and abstain from contact with others, except in exceptional circumstances (7,8). A recently published TILDA report outlining the incidence of loneliness among those aged 50 years and over in Ireland, shows 7% experience emotional loneliness on a frequent basis, and almost one in three experience emotional loneliness at least some of the time (9). It is likely the introduction of social distancing and self-isolation measures will exacerbate loneliness, given that one of the commonest causes of loneliness is social isolation. Internet use offers an effective method of alleviating some of the negative consequences of these measures by enabling virtual interactions (10). Moreover, the use of internet by institutions and organisations as a platform for information distribution, access to support services and the continuation of commerce during the COVID-19 pandemic has increased substantially (11-14). In this context, this report will outline internet access and use among adults aged 50 years and over in Ireland, using population estimates derived from data collected during Wave 5 of TILDA in 2018, in conjunction with the most recent 2016 Census data. Specifically, information will be provided regarding home access to the internet; access to smartphones/tablets (ergo access to apps); and the frequency and purpose of internet use. This report will also provide information regarding those who are solely reliant on internet access external to their own homes, as well as the lack of internet access among those living alone.
PUBLISHED
doi: https://www.doi.org/10.38018/TildaRe.2020-06
Keywords: Ageing